2017
DOI: 10.2147/ndt.s136950
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the short form of the Coping Inventory for Stressful Situations into Chinese

et al.

Abstract: ObjectivesThe Coping Inventory for Stressful Situations (CISS) is a measurement tool for evaluating stress that has good psychometric properties. We investigated the applicability of a short-form version of the CISS in a large sample of Chinese university students.MethodsNine hundred and seventy-two Chinese university students aged 18–30 years (mean =20.15, standard deviation =3.26) were chosen as subjects, of whom 101 were randomly selected to be retested after a 2-week interval.ResultsThe results of a confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In addition, this study showed that a higher emotionoriented coping style significantly increases the risk of developing depression in both patients and healthy age-matched controls. According to the current literature, increases in depression symptoms are related to a person's preference for emotion-oriented rather than task-oriented coping strategies [43], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this study showed that a higher emotionoriented coping style significantly increases the risk of developing depression in both patients and healthy age-matched controls. According to the current literature, increases in depression symptoms are related to a person's preference for emotion-oriented rather than task-oriented coping strategies [43], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Higher scores indicate a greater use of coping strategies (Endler & Parker, 1990). It is a sound psychometric instrument with Cronbach’s α : task‐focused = .78–.87, emotion‐focused = .78–.87, and avoidant coping = .70–.80 and has been validated for adolescents (Li, Liu, Hu, & Jin, 2017).…”
Section: Methodsmentioning
confidence: 99%
“… Safety Attitudes Questionnaire (SAQ) [ 81 , 82 ] Wisconsin Card Sorting Test (WCST) [ 57 , 83 ]. Coping Inventory of Task Stress (CITS) [ 31 , 84 ]. Subjective Mental Effort Questionnaire (SMEQ) [ 85 ].…”
Section: Technical Approaches For Non-technical Skill and Mental Workload Assessment In Ramismentioning
confidence: 99%
“…MRQ estimates workload with 17 items, and it is specifically useful for multitasking workload measurements [ 77 ]. SSSQ is based on DSSQ, and both target stress measurement [ 86 ], such as CITS [ 84 ]. RSME and SMEQ estimate mental effort on a 9-point scale from extreme effort to absolutely no effort.…”
Section: Technical Approaches For Non-technical Skill and Mental Workload Assessment In Ramismentioning
confidence: 99%
See 1 more Smart Citation